Upaya Menurunkan Tingkat Perkawinan Dibawah Umur Terhadap Hak Pendidikan Formal Anak (Ajudikasi : Jurnal Ilmu Hukum, 2019)
This research is motivated by underage marriage problems because many children who carry out underage marriages and do not attach importance to education.This research method is descriptive with factual depiction, the data in the form of language and discourse expressions are appropriate and systematic, qualitative research is a research that is used to examine the condition of scientific objects, where the researcher is a key instrument.The results of this study indicate that there are impacts caused by underage marriage in Cireundeu Village, namely divorce and health problems, while the factors that influence the occurrence of underage marriage, namely economic factors, education, parents and promiscuity, as for efforts to reduce the marriage rate underage towards the right of formal education of children, namely by improving the quality of education that education has a good future for those who take it, then socializing the boundaries of the age of marriage, the impact and danger of underage marriage, and socializing compulsory 12-year education affect the level of graduate children so that children can continue their education to the upper secondary level and can improve their quality of life.